An unusual case of respiratory failure in a patient with Randu–Osler–Weber disease. Case report - Valery I. Podzolkov; Anna E. Pokrovskaya; Victoria S. Ivanova; Kseniya E. Krylova; Polina V. Luchkina; Fatima E. Murzakhanova; Darya D. Gerasimova; Ivan D. Medvedev (Consilium Medicum)
Clinical observation is of interest due to the shift in the vector of the main complaints of the classic manifestation of Randu–Osler–Weber disease in the form of epistaxis and anemia syndrome towards the syndrome of severe respiratory failure, the cause of which is the presence of arteriovenous malformations in the lungs. The importance of an interdisciplinary approach to the diagnosis and treatment of patients with Randu–Osler–Weber disease is discussed.